Impact of p53-associated acute myeloid leukemia hallmarks on metabolism and the immune environment - Chomczyk, Monika; Gazzola, Luca; Dash, Shubhankar; Firmanty, Patryk; George, Binsah S.; Mohanty, Vakul; Abbas, Hussein A.; Baran, Natalia (Frontiers in Pharmacology, 2024)
Acute myeloid leukemia (AML), an aggressive malignancy of hematopoietic stem cells, is characterized by the blockade of cell differentiation, uncontrolled proliferation, and cell expansion that impairs healthy hematopoiesis and results in pancytopenia and susceptibility to infections. Several genetic and chromosomal aberrations play a role in AML and influence patient outcomes. TP53 is a key tumor suppressor gene involved in a variety of cell features, such as cell-cycle regulation, genome stability, proliferation, differentiation, stem-cell homeostasis, apoptosis, metabolism, senescence, and the repair of DNA damage in response to cellular stress. In AML, TP53 alterations occur in 5%–12% of de novo AML cases. These mutations form an important molecular subgroup, and patients with these mutations have the worst prognosis and shortest overall survival among patients with AML, even when treated with aggressive chemotherapy and allogeneic stem cell transplant. The frequency of TP53-mutations increases in relapsed and recurrent AML and is associated with chemoresistance. Progress in AML genetics and biology has brought the novel therapies, however, the clinical benefit of these agents for patients whose disease is driven by TP53 mutations remains largely unexplored. This review focuses on the molecular characteristics of TP53-mutated disease; the impact of TP53 on selected hallmarks of leukemia, particularly metabolic rewiring and immune evasion, the clinical importance of TP53 mutations; and the current progress in the development of preclinical and clinical therapeutic strategies to treat TP53-mutated disease.